ChemInform Abstract: Thioacids Mediated Selective and Mild N‐Acylation of Amines. Issue 39 (5th September 2013) - Mali, Sachitanand M.; Bhaisare, Rupal D.; Gopi, Hosahudya N.
Abstract The new method proceeds under mild conditions within very short reaction times and is applicable to a wide range of aromatic and aliphatic amines bearing various functional groups.